How to develop emotional health - James, Oliver, ....- (London : Macmillan, 2014)
Happiness is a loaded term that means different things to different people. To some, it might mean life satisfaction, to others, a fleeting moment of joy. Rather than seeking to be happy, Oliver James encourages us to cultivate our emotional health. Outlining the five elements of good emotional health - insightfulness, a strong sense of self, fluid relationships, authenticity and playfulness in our approach to life - he offers strategies for optimizing each characteristic to live more fulfilling lives. Helping us to understand the impact our emotional baggage has on our daily interactions, he reveals how to overcome unhelpful patterns and become more self-aware - revitalizing our approach to life.
Keywords: Zelfontplooiing